Aspectos da Impenhorabilidade da Pequena Propriedade Rural e o Desenvolvimento Rural: Garantia Constitucional da Agricultura Familiar - Elia Denise Hammes (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2017)
The aim of this paper is to analyze the opening of the family farm to the market, and from this reality to verify the importance of the constitutional guarantee of unseizability of small farms, paying attention to important aspects regarding to the interpretation of the Judiciary. Considered for methodological issues of this article, documentary research along with an analytical-descriptive analysis based on secondary data as laws and jurisprudence which were collected on governmental websites. The Federal Constitution of 1988, in an unprecedented manner, established the small farm, since exploited by the family, as well absolutely unseizable to debts generated as a result of their productive activity. The importance of family agriculture for the country has been verified and it has been shown that the judiciary in its bodies comes, as a rule, participating in the maintenance of the family farmer in the small rural property, without losing it due to its debts, made in view of its productive activity, applying not only the constitutional principles, but also the infra-constitutional legislation.